Quality of life of caregivers for patients of cerebrovascular accidents: association of (socio-demographic) characteristics and burden - Tatiana Ferreira da Costa; Kátia Nêyla de Freitas Macêdo Costa; Maria das Graças Melo Fernandes; Kaisy Pereira Martins; Silmery da Silva Brito (SciELO, 2015)
OBJECTIVE Investigating the association between quality of life with socio-demographic characteristics and the burden of caregivers for individuals with cerebrovascular accident sequelae. METHOD A descriptive, cross-sectional study with a sample composed of 136 caregivers. For data collection, a semi-structured questionnaire, the Barthel, Burden Interview and Short-Form-36 scales were used. Correlation analysis, t-Student test and F-test were used for the analysis in order to compare averages. RESULTS Significant averages in quality of life were demonstrated in association with female caregivers and those over 60 years in the field 'functional capacity,' and in the domains of 'mental health' and 'vitality' for those with higher income. Regarding burden association, the highlighted areas were 'functional capacity,' 'physical aspects,' 'emotional aspects' and 'pain.' CONCLUSION The creation of public policies and social support to effectively reduce the burden on caregivers is a necessity.